Analisis Implementasi Sifat Rasulullah Dalam Pengelolaan Zakat - Syahroni, Denti Firdayanti Awaliah; Sulaeman, Sulaeman; Noor, Iqbal (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2020)
This study aims to discuss implementation the characteristic of Muhammad in the management of zakat carried out by the Amil Zakat Board in Sukabumi City. This research uses a descriptive method with a qualitative approach. The results of this study indicate that the National Amil Zakat Board of Sukabumi City has implemented the characteristics of the Muhammad such as shidiq, amanah, tabligh, and fathanah in the management of zakat. This implementation is very important to be applied by every amil zakat because in the management of zakat the relationship is not only with humans but also with Allah SWT.